Effect of integrated nutrient management in pearl millet (Pennisetum glaucum)- wheat (Triticum aestivum) system under water saline irrigation - PRAKASH, RAM; DHANDA, ANKUSH; KUMAR, RAKESH; RANI, SARITRA; KUMAR, SHITAL (The Indian Journal of Agricultural Sciences, 2025)
Salinity predominates in the arid and semi-arid regions which negatively affects the crops yield, nutrient availability, and microbes present in the soil. The present study was carried out during 2019–2021 at Chaudhary Charan Singh Haryana Agriculture University, Hisar, Haryana to access the effect of saline irrigation water on performance of pearl millet [Pennisetum glaucum (L.) R. Br.]-wheat (Triticum aestivum L.) cropping system while using organic manures. The varieties HHB226 and WH 1105 of pearl millet and wheat were taken for the experiment, respectively The experiment was conducted in a randomized block design (RBD) comprised of 12 treatments, viz. 75% RDF (T1); 100% RDF (T2); 75% RDF + salinity strain (ST3) (T3); 100% RDF + ST3 (T4); 75% RDF + 2.5 t/ha biogas slurry (BS) + ST3 (T5); 100% RDF + 2.5 t/ha biogas slurry (BS) + ST3 (T6); 75% RDF + 2.5 t/ha vermicompost + ST3 (T7); 100% RDF + 2.5 t/ha vermicompost + ST3 (T8); 75% RDF + 10 t/ha FYM + biomix (T9); 100% RDF + 10 t/ha FYM + biomix (T10); 75% RDF + 2.5 t/ha vermicompost + biomix (T11); 100% RDF + 2.5 t/ha vermicompost + biomix (T12). The results revealed that the crop responded better to salt stress where organic manures were incorporated. The highest grain and straw yields of both crops were attained with treatment T10 (100% RDF + 10 t/ha FYM + biomix) being at par with treatments T12, T8 and T6. The soil properties were found improved in term of NPK availability and other microbiological parameter under manurial treatments compared to control and solely applied chemical fertilizers. Salinity stress was considerably decreased when organic manures were used either alone or in conjunction with mineral fertilizers.